Prove mu-is-nt for DeltaM with fmap-equiv
author Yasutaka Higa Tue, 03 Feb 2015 11:45:33 +0900 6dcc68ef8f96 d56596e4e784
line wrap: on
line source
```
open import Level
open import Relation.Binary.PropositionalEquality
open ≡-Reasoning

open import basic
open import delta
open import delta.functor
open import deltaM
open import deltaM.functor
open import nat
open import laws

open Functor
open NaturalTransformation

-- sub proofs

deconstruct-id : {l : Level} {A : Set l} {n : Nat}
{T : Set l -> Set l} {F : Functor T} {M : Monad T F} ->
(d : DeltaM M A (S n)) -> deltaM (unDeltaM d) ≡ d
deconstruct-id {n = O}   (deltaM x) = refl
deconstruct-id {n = S n} (deltaM x) = refl

headDeltaM-with-f : {l : Level} {A B : Set l} {n : Nat}
{T : Set l -> Set l} {F : Functor T} {M : Monad T F}
(f : A -> B) -> (x : (DeltaM M A (S n))) ->
((fmap F f) ∙ headDeltaM) x ≡ (headDeltaM ∙ (deltaM-fmap f)) x
headDeltaM-with-f {n = O} f   (deltaM (mono x))    = refl
headDeltaM-with-f {n = S n} f (deltaM (delta x d)) = refl

tailDeltaM-with-f : {l : Level} {A B : Set l} {n : Nat}
{T : Set l -> Set l} {F : Functor T} {M : Monad T F}
(f : A -> B) -> (d : (DeltaM M A (S (S n)))) ->
(tailDeltaM ∙ (deltaM-fmap f)) d ≡ ((deltaM-fmap f) ∙ tailDeltaM) d
tailDeltaM-with-f {n = O} f (deltaM (delta x d))   = refl
tailDeltaM-with-f {n = S n} f (deltaM (delta x d)) = refl

fmap-headDeltaM-with-deltaM-eta : {l : Level} {A : Set l} {n : Nat}
{T : Set l -> Set l} {F : Functor T} {M : Monad T F} ->
(x : T A) -> (fmap F ((headDeltaM {n = n} {M = M}) ∙ deltaM-eta) x) ≡ fmap F (eta M) x
fmap-headDeltaM-with-deltaM-eta {n = O}   x = refl
fmap-headDeltaM-with-deltaM-eta {n = S n} x = refl

fmap-tailDeltaM-with-deltaM-eta : {l : Level} {A : Set l} {n : Nat}
{T : Set l -> Set l} {F : Functor T} {M : Monad T F} ->
(d : DeltaM M A (S n)) ->
deltaM-fmap ((tailDeltaM {n = n} {M = M} ) ∙ deltaM-eta) d ≡ deltaM-fmap (deltaM-eta) d
fmap-tailDeltaM-with-deltaM-eta {n = O}   d = refl
fmap-tailDeltaM-with-deltaM-eta {n = S n} d = refl

fmap-headDeltaM-with-deltaM-mu : {l : Level} {A : Set l} {n : Nat}
{T : Set l -> Set l} {F : Functor T} {M : Monad T F} ->
(x : T (DeltaM M (DeltaM M A (S n)) (S n))) ->
fmap F (headDeltaM ∙ deltaM-mu) x ≡ fmap F (((mu M) ∙ (fmap F headDeltaM)) ∙ headDeltaM) x
fmap-headDeltaM-with-deltaM-mu {n = O}   x = refl
fmap-headDeltaM-with-deltaM-mu {n = S n} x = refl

fmap-tailDeltaM-with-deltaM-mu : {l : Level} {A : Set l} {n : Nat}
{T : Set l -> Set l} {F : Functor T} {M : Monad T F} ->
(d : DeltaM M (DeltaM M (DeltaM M A (S (S n))) (S (S n))) (S n)) ->
deltaM-fmap (tailDeltaM ∙ deltaM-mu) d ≡ deltaM-fmap ((deltaM-mu ∙ (deltaM-fmap tailDeltaM)) ∙ tailDeltaM) d
fmap-tailDeltaM-with-deltaM-mu {n = O} (deltaM (mono x)) = refl
fmap-tailDeltaM-with-deltaM-mu {n = S n} (deltaM d)      = refl

-- main proofs

deltaM-eta-is-nt : {l : Level} {A B : Set l} {n : Nat}
{T : Set l -> Set l} {F : Functor T} {M : Monad T F} ->
(f : A -> B) -> (x : A) ->
((deltaM-eta {l} {B} {n} {T} {F} {M} )∙ f) x ≡ deltaM-fmap f (deltaM-eta x)
deltaM-eta-is-nt {l} {A} {B} {O} {M} {fm} {mm} f x   = begin
deltaM-eta {n = O} (f x)              ≡⟨ refl ⟩
deltaM (mono (eta mm (f x)))          ≡⟨ cong (\de -> deltaM (mono de)) (eta-is-nt mm f x) ⟩
deltaM (mono (fmap fm f (eta mm x)))  ≡⟨ refl ⟩
deltaM-fmap f (deltaM-eta {n = O} x)  ∎
deltaM-eta-is-nt {l} {A} {B} {S n} {M} {fm} {mm} f x = begin
deltaM-eta {n = S n} (f x)
≡⟨ refl ⟩
deltaM (delta-eta {n = S n} (eta mm (f x)))
≡⟨ refl ⟩
deltaM (delta (eta mm (f x)) (delta-eta (eta mm (f x))))
≡⟨ cong (\de -> deltaM (delta de (delta-eta de))) (eta-is-nt mm f x) ⟩
deltaM (delta (fmap fm f (eta mm x)) (delta-eta (fmap fm f (eta mm x))))
≡⟨ cong (\de ->  deltaM (delta (fmap fm f (eta mm x)) de)) (eta-is-nt delta-is-monad (fmap fm f) (eta mm x)) ⟩
deltaM (delta (fmap fm f (eta mm x)) (delta-fmap (fmap fm f) (delta-eta (eta mm x))))
≡⟨ refl ⟩
deltaM-fmap f (deltaM-eta {n = S n} x)
∎

deltaM-mu-is-nt : {l : Level} {A B : Set l} {n : Nat}
{T : Set l -> Set l} {F : Functor T} {M : Monad T F}
(f : A -> B) -> (d : DeltaM M (DeltaM M A (S n)) (S n)) ->
deltaM-fmap f (deltaM-mu d) ≡ deltaM-mu (deltaM-fmap (deltaM-fmap f) d)
deltaM-mu-is-nt {l} {A} {B} {O} {T} {F} {M}  f (deltaM (mono x))      =
{-
deltaM-mu-is-nt {l} {A} {B} {O} {T} {F} {M}  f (deltaM (mono x))      = begin
deltaM-fmap f (deltaM-mu (deltaM (mono x))) ≡⟨ refl ⟩
deltaM-fmap f (deltaM (mono (mu M (fmap F (headDeltaM {M = M}) (headDeltaM {M = M} (deltaM (mono x))))))) ≡⟨ refl ⟩
deltaM-fmap f (deltaM (mono (mu M (fmap F (headDeltaM {M = M}) x)))) ≡⟨ refl ⟩
deltaM (mono (fmap F f (mu M (fmap F (headDeltaM {M = M}) x)))) ≡⟨ {!!} ⟩
deltaM (mono (mu M (fmap F (headDeltaM {M = M}) (fmap F (deltaM-fmap f) x)))) ≡⟨ refl ⟩
deltaM (mono (mu M (fmap F (headDeltaM {M = M}) (headDeltaM {M = M} (deltaM (mono (fmap F (deltaM-fmap f) x))))))) ≡⟨ refl ⟩
deltaM-mu (deltaM (mono (fmap F (deltaM-fmap f) x))) ≡⟨ refl ⟩
deltaM-mu (deltaM (mono (fmap F (deltaM-fmap f) x))) ≡⟨ refl ⟩
deltaM-mu (deltaM-fmap (deltaM-fmap f) (deltaM (mono x)))
∎
-}

begin
deltaM-fmap f (deltaM-mu (deltaM (mono x)))
≡⟨ refl ⟩
deltaM-fmap f (deltaM (mono (mu M (fmap F headDeltaM x))))
≡⟨ refl ⟩
deltaM (mono (fmap F f (mu M (fmap F headDeltaM x))))
≡⟨ cong (\de -> deltaM (mono de)) (sym (mu-is-nt M f (fmap F headDeltaM x))) ⟩
deltaM (mono (mu M (fmap F (fmap F f) (fmap F headDeltaM x))))
≡⟨ cong (\de -> deltaM (mono (mu M de))) (sym (covariant F headDeltaM (fmap F f) x)) ⟩
deltaM (mono (mu M (fmap F ((fmap F f) ∙ headDeltaM) x)))
≡⟨ cong (\de -> deltaM (mono (mu M de))) (fmap-equiv F (headDeltaM-with-f f) x) ⟩
deltaM (mono (mu M (fmap F ((headDeltaM {M = M}) ∙ (deltaM-fmap f)) x)))
≡⟨ cong (\de -> deltaM (mono (mu M de))) (covariant F (deltaM-fmap f) (headDeltaM) x) ⟩
deltaM (mono (mu M (fmap F (headDeltaM {M = M}) (fmap F (deltaM-fmap f) x))))
≡⟨ refl ⟩
deltaM (mono (mu M (fmap F (headDeltaM {M = M}) (headDeltaM {M = M} (deltaM (mono (fmap F (deltaM-fmap f) x)))))))
≡⟨ refl ⟩
deltaM-mu (deltaM (mono (fmap F (deltaM-fmap f) x)))
≡⟨ refl ⟩
deltaM-mu (deltaM-fmap (deltaM-fmap f) (deltaM (mono x)))
∎

deltaM-mu-is-nt {l} {A} {B} {S n} {T} {F} {M} f (deltaM (delta x d)) = begin
deltaM-fmap f (deltaM-mu (deltaM (delta x d))) ≡⟨ refl ⟩
deltaM-fmap f (deltaM (delta (mu M (fmap F (headDeltaM {M = M}) (headDeltaM {M = M} (deltaM (delta x d)))))
(unDeltaM {M = M} (deltaM-mu (deltaM-fmap tailDeltaM (tailDeltaM (deltaM (delta x d))))))))
≡⟨ refl ⟩
deltaM-fmap f (deltaM (delta (mu M (fmap F (headDeltaM {M = M}) x))
(unDeltaM {M = M} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM d))))))
≡⟨ refl ⟩
deltaM (delta (fmap F f (mu M (fmap F (headDeltaM {M = M}) x)))
(delta-fmap (fmap F f) (unDeltaM {M = M} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM d))))))
≡⟨ cong (\de -> deltaM (delta de
(delta-fmap (fmap F f) (unDeltaM {M = M} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM d)))))))
(sym (mu-is-nt M f (fmap F headDeltaM x)))  ⟩
deltaM (delta (mu M (fmap F (fmap F f) (fmap F (headDeltaM {M = M}) x)))
(delta-fmap (fmap F f) (unDeltaM {M = M} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM d))))))
≡⟨ cong (\de -> deltaM (delta (mu M de) (delta-fmap (fmap F f) (unDeltaM {M = M} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM d)))))))
(sym (covariant F headDeltaM (fmap F f) x)) ⟩
deltaM (delta (mu M (fmap F ((fmap F f) ∙ (headDeltaM {M = M})) x))
(delta-fmap (fmap F f) (unDeltaM {M = M} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM d))))))
≡⟨ cong (\de -> deltaM (delta (mu M de) (delta-fmap (fmap F f) (unDeltaM {M = M} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM d)))))))
(fmap-equiv F (headDeltaM-with-f f) x)  ⟩
deltaM (delta (mu M (fmap F ((headDeltaM {M = M}) ∙ (deltaM-fmap f)) x))
(delta-fmap (fmap F f) (unDeltaM {M = M} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM d))))))
≡⟨ refl ⟩
deltaM (delta (mu M (fmap F ((headDeltaM {M = M}) ∙ (deltaM-fmap f)) x))
(unDeltaM {M = M} (deltaM-fmap f (deltaM-mu (deltaM-fmap tailDeltaM (deltaM d))))))
≡⟨ cong (\de -> deltaM (delta (mu M (fmap F ((headDeltaM {M = M}) ∙ (deltaM-fmap f)) x)) (unDeltaM de)))
(deltaM-mu-is-nt {l} {A} {B} {n} {T} {F} {M} f (deltaM-fmap tailDeltaM (deltaM d))) ⟩
deltaM (delta (mu M (fmap F ((headDeltaM {M = M}) ∙ (deltaM-fmap f)) x))
(unDeltaM {M = M} (deltaM-mu (deltaM-fmap (deltaM-fmap {n = n} f) (deltaM-fmap {n = n} (tailDeltaM {n = n}) (deltaM d))))))
≡⟨ cong (\de -> deltaM (delta (mu M (fmap F ((headDeltaM {M = M}) ∙ (deltaM-fmap f)) x)) (unDeltaM {M = M} (deltaM-mu de))))
(sym (deltaM-covariant (deltaM-fmap f) tailDeltaM (deltaM d))) ⟩
deltaM (delta (mu M (fmap F ((headDeltaM {M = M}) ∙ (deltaM-fmap f)) x))
(unDeltaM {M = M} (deltaM-mu (deltaM-fmap {n = n} ((deltaM-fmap {n = n} f) ∙ (tailDeltaM {n = n})) (deltaM d)))))

≡⟨ cong (\de -> deltaM (delta (mu M (fmap F ((headDeltaM {M = M}) ∙ (deltaM-fmap f)) x)) (unDeltaM {M = M} (deltaM-mu de))))
(sym (deltaM-fmap-equiv (tailDeltaM-with-f f) (deltaM d))) ⟩
deltaM (delta (mu M (fmap F ((headDeltaM {M = M}) ∙ (deltaM-fmap f)) x))
(unDeltaM {M = M} (deltaM-mu (deltaM-fmap (tailDeltaM ∙ (deltaM-fmap f)) (deltaM d)))))
≡⟨ cong (\de -> deltaM (delta (mu M (fmap F ((headDeltaM {M = M}) ∙ (deltaM-fmap f)) x)) (unDeltaM {M = M} (deltaM-mu de))))
(deltaM-covariant tailDeltaM (deltaM-fmap f) (deltaM d)) ⟩
deltaM (delta (mu M (fmap F ((headDeltaM {M = M}) ∙ (deltaM-fmap f)) x))
(unDeltaM {M = M} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM-fmap (deltaM-fmap f) (deltaM d))))))
≡⟨ refl ⟩
deltaM (delta (mu M (fmap F ((headDeltaM {M = M}) ∙ (deltaM-fmap f)) x))
(unDeltaM {M = M} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-fmap (fmap F (deltaM-fmap f)) d))))))
≡⟨ cong (\de -> deltaM (delta (mu M de) (unDeltaM {M = M} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-fmap (fmap F (deltaM-fmap f)) d)))))))
(covariant F (deltaM-fmap f) headDeltaM x) ⟩
deltaM (delta (mu M (fmap F (headDeltaM {M = M}) (fmap F (deltaM-fmap f) x)))
(unDeltaM {M = M} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-fmap (fmap F (deltaM-fmap f)) d))))))
≡⟨ refl ⟩
deltaM (delta (mu M (fmap F (headDeltaM {M = M}) (headDeltaM {M = M} (deltaM (delta (fmap F (deltaM-fmap f) x) (delta-fmap (fmap F (deltaM-fmap f)) d))))))
(unDeltaM {M = M} (deltaM-mu (deltaM-fmap tailDeltaM (tailDeltaM (deltaM (delta (fmap F (deltaM-fmap f) x) (delta-fmap (fmap F (deltaM-fmap f)) d))))))))
≡⟨ refl ⟩
deltaM-mu (deltaM (delta (fmap F (deltaM-fmap f) x) (delta-fmap (fmap F (deltaM-fmap f)) d)))
≡⟨ refl ⟩
deltaM-mu (deltaM-fmap (deltaM-fmap f) (deltaM (delta x d)))
∎

{-
deltaM-right-unity-law : {l : Level} {A : Set l} {n : Nat}
{T : Set l -> Set l} {F : Functor T} {M : Monad T F} ->
(d : DeltaM M A (S n)) -> (deltaM-mu ∙ deltaM-eta) d ≡ id d
deltaM-right-unity-law {l} {A} {O} {M} {fm} {mm} (deltaM (mono x)) = begin
deltaM-mu (deltaM-eta (deltaM (mono x)))             ≡⟨ refl ⟩
deltaM-mu (deltaM (mono (eta mm (deltaM (mono x))))) ≡⟨ refl ⟩
deltaM (mono (mu mm (fmap fm (headDeltaM {M = mm})(eta mm (deltaM (mono x))))))
≡⟨ cong (\de -> deltaM (mono (mu mm de))) (sym (eta-is-nt mm headDeltaM (deltaM (mono x)) )) ⟩
deltaM (mono (mu mm (eta mm ((headDeltaM {l} {A} {O} {M} {fm} {mm}) (deltaM (mono x)))))) ≡⟨ refl ⟩
deltaM (mono (mu mm (eta mm x))) ≡⟨ cong (\de -> deltaM (mono de)) (sym (right-unity-law mm x)) ⟩
deltaM (mono x)
∎
deltaM-right-unity-law {l} {A} {S n} {T} {F} {M} (deltaM (delta x d)) = begin
deltaM-mu (deltaM-eta (deltaM (delta x d)))
≡⟨ refl ⟩
deltaM-mu (deltaM (delta (eta M (deltaM (delta x d))) (delta-eta (eta M (deltaM (delta x d))))))
≡⟨ refl ⟩
deltaM (delta (mu M (fmap F (headDeltaM {M = M}) (headDeltaM {M = M} (deltaM (delta {l} {T (DeltaM M A (S (S n)))} {n} (eta M (deltaM (delta x d))) (delta-eta (eta M (deltaM (delta x d)))))))))
(unDeltaM {M = M} (deltaM-mu (deltaM-fmap tailDeltaM (tailDeltaM (deltaM (delta (eta M (deltaM (delta x d))) (delta-eta (eta M (deltaM (delta x d)))))))))))
≡⟨ refl ⟩
deltaM (delta (mu M (fmap F (headDeltaM {M = M}) (eta M (deltaM (delta x d)))))
(unDeltaM {M = M} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-eta (eta M (deltaM (delta x d)))))))))
≡⟨ cong (\de -> deltaM (delta (mu M de)
(unDeltaM {M = M} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-eta (eta M (deltaM (delta x d))))))))))
(sym (eta-is-nt M headDeltaM (deltaM (delta x d)))) ⟩
deltaM (delta (mu M (eta M (headDeltaM {M = M} (deltaM (delta x d)))))
(unDeltaM {M = M} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-eta (eta M (deltaM (delta x d)))))))))
≡⟨ refl ⟩
deltaM (delta (mu M (eta M x))
(unDeltaM {M = M} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-eta (eta M (deltaM (delta x d)))))))))
≡⟨ cong (\de -> deltaM (delta de (unDeltaM {M = M} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-eta (eta M (deltaM (delta x d))))))))))
(sym (right-unity-law M x)) ⟩
deltaM (delta x (unDeltaM {M = M} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-eta (eta M (deltaM (delta x d)))))))))
≡⟨ refl ⟩
deltaM (delta x (unDeltaM {M = M} (deltaM-mu (deltaM (delta-fmap (fmap F tailDeltaM) (delta-eta (eta M (deltaM (delta x d)))))))))
≡⟨ cong (\de -> deltaM (delta x (unDeltaM {M = M} (deltaM-mu (deltaM de)))))
(sym (delta-eta-is-nt (fmap F tailDeltaM)  (eta M (deltaM (delta x d))))) ⟩
deltaM (delta x (unDeltaM {M = M} (deltaM-mu (deltaM (delta-eta (fmap F tailDeltaM (eta M (deltaM (delta x d)))))))))
≡⟨ cong (\de -> deltaM (delta x (unDeltaM {M = M} (deltaM-mu (deltaM (delta-eta de))))))
(sym (eta-is-nt M tailDeltaM (deltaM (delta x d)))) ⟩
deltaM (delta x (unDeltaM {M = M} (deltaM-mu (deltaM (delta-eta (eta M (tailDeltaM (deltaM (delta x d)))))))))
≡⟨ refl ⟩
deltaM (delta x (unDeltaM {M = M} (deltaM-mu (deltaM (delta-eta (eta M (deltaM d)))))))
≡⟨ refl ⟩
deltaM (delta x (unDeltaM {M = M} (deltaM-mu (deltaM-eta (deltaM d)))))
≡⟨ cong (\de -> deltaM (delta x (unDeltaM {M = M} de))) (deltaM-right-unity-law (deltaM d)) ⟩
deltaM (delta x (unDeltaM {M = M} (deltaM d)))
≡⟨ refl ⟩
deltaM (delta x d)
∎

postulate deltaM-left-unity-law : {l : Level} {A : Set l}
{M : Set l -> Set l} {functorM : Functor M} {monadM : Monad M functorM}
{n : Nat}
(d : DeltaM M {functorM} {monadM} A (S n)) ->
(deltaM-mu ∙ (deltaM-fmap deltaM-eta)) d ≡ id d
{-
deltaM-left-unity-law {l} {A} {M} {fm} {mm} {O} (deltaM (mono x))      = begin
deltaM-mu (deltaM-fmap deltaM-eta (deltaM (mono x)))
≡⟨ refl ⟩
deltaM-mu (deltaM (delta-fmap (fmap fm deltaM-eta) (mono x)))
≡⟨ refl ⟩
deltaM-mu (deltaM (mono (fmap fm deltaM-eta x)))
≡⟨ refl ⟩
deltaM (mono (mu mm (fmap fm (headDeltaM {l} {A} {O} {M}) (fmap fm deltaM-eta x))))
≡⟨ cong (\de -> deltaM (mono (mu mm de))) (sym (covariant fm deltaM-eta headDeltaM x)) ⟩
deltaM (mono (mu mm (fmap fm ((headDeltaM {l} {A} {O} {M} {fm} {mm}) ∙ deltaM-eta) x)))
≡⟨ cong (\de -> deltaM (mono (mu mm de))) (fmap-headDeltaM-with-deltaM-eta {l} {A} {O} {M} {fm} {mm} x) ⟩
deltaM (mono (mu mm (fmap fm (eta mm) x)))
≡⟨ cong (\de -> deltaM (mono de)) (left-unity-law mm x) ⟩
deltaM (mono x)
∎
deltaM-left-unity-law {l} {A} {M} {fm} {mm} {S n} (deltaM (delta x d)) = begin
deltaM-mu (deltaM-fmap deltaM-eta (deltaM (delta x d)))
≡⟨ refl ⟩
deltaM-mu (deltaM (delta-fmap (fmap fm deltaM-eta) (delta x d)))
≡⟨ refl ⟩
deltaM-mu (deltaM (delta (fmap fm deltaM-eta x) (delta-fmap (fmap fm deltaM-eta) d)))
≡⟨ refl  ⟩
appendDeltaM (deltaM (mono (mu mm (fmap fm (headDeltaM {l} {A} {S n} {M} {fm} {mm}) (fmap fm deltaM-eta x)))))
(deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-fmap (fmap fm deltaM-eta) d))))
≡⟨ cong (\de -> appendDeltaM (deltaM (mono (mu mm de)))
(deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-fmap (fmap fm deltaM-eta) d)))))
(sym (covariant fm deltaM-eta headDeltaM x)) ⟩
appendDeltaM (deltaM (mono (mu mm (fmap fm ((headDeltaM {l} {A} {S n} {M} {fm} {mm}) ∙ deltaM-eta) x))))
(deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-fmap (fmap fm deltaM-eta) d))))
≡⟨ cong (\de -> appendDeltaM (deltaM (mono (mu mm de)))
(deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-fmap (fmap fm deltaM-eta) d)))))
(fmap-headDeltaM-with-deltaM-eta {l} {A} {S n} {M} {fm} {mm} x) ⟩
appendDeltaM (deltaM (mono (mu mm (fmap fm (eta mm) x))))
(deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-fmap (fmap fm deltaM-eta) d))))

≡⟨ cong (\de -> (appendDeltaM (deltaM (mono de)) (deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-fmap (fmap fm deltaM-eta) d))))))
(left-unity-law mm x) ⟩
appendDeltaM (deltaM (mono x)) (deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-fmap (fmap fm deltaM-eta) d))))
≡⟨ refl ⟩
appendDeltaM (deltaM (mono x)) (deltaM-mu (deltaM-fmap (tailDeltaM {n = n})(deltaM-fmap deltaM-eta (deltaM d))))
≡⟨ cong (\de -> appendDeltaM (deltaM (mono x)) (deltaM-mu de)) (sym (covariant deltaM-is-functor deltaM-eta tailDeltaM (deltaM d))) ⟩
appendDeltaM (deltaM (mono x)) (deltaM-mu (deltaM-fmap ((tailDeltaM {n = n}) ∙ deltaM-eta) (deltaM d)))
≡⟨ cong (\de -> appendDeltaM (deltaM (mono x)) (deltaM-mu de)) (fmap-tailDeltaM-with-deltaM-eta (deltaM d)) ⟩
appendDeltaM (deltaM (mono x)) (deltaM-mu (deltaM-fmap deltaM-eta (deltaM d)))
≡⟨ cong (\de -> appendDeltaM (deltaM (mono x)) de) (deltaM-left-unity-law (deltaM d)) ⟩
appendDeltaM (deltaM (mono x)) (deltaM d)
≡⟨ refl ⟩
deltaM (delta x d)
∎

-}
postulate nya : {l : Level} {A : Set l}
(M : Set l -> Set l) (fm : Functor M) (mm : Monad M fm)
(d : DeltaM M {fm} {mm} (DeltaM M {fm} {mm} (DeltaM M {fm} {mm} A (S O)) (S O))  (S O)) ->
deltaM-mu (deltaM-fmap deltaM-mu d) ≡ deltaM-mu (deltaM-mu d)

deltaM-association-law : {l : Level} {A : Set l} {n : Nat}
(M : Set l -> Set l) (fm : Functor M) (mm : Monad M fm)
(d : DeltaM M {fm} {mm} (DeltaM M {fm} {mm} (DeltaM M {fm} {mm} A (S n)) (S n))  (S n)) ->
deltaM-mu (deltaM-fmap deltaM-mu d) ≡ deltaM-mu (deltaM-mu d)
deltaM-association-law {l} {A} {O} M fm mm (deltaM (mono x))    = nya {l} {A} M fm mm (deltaM (mono x))
{-
begin
deltaM-mu (deltaM-fmap deltaM-mu (deltaM (mono x))) ≡⟨ refl ⟩
deltaM-mu (deltaM (mono (fmap fm deltaM-mu x))) ≡⟨ refl ⟩
deltaM (mono (mu mm (fmap fm headDeltaM (headDeltaM {A = DeltaM M A (S O)} {monadM = mm} (deltaM (mono (fmap fm deltaM-mu x))))))) ≡⟨ refl ⟩
deltaM (mono (mu mm (fmap fm headDeltaM (fmap fm deltaM-mu x)))) ≡⟨ refl ⟩
deltaM (mono (mu mm (fmap fm (headDeltaM {A = A} {monadM = mm}) (fmap fm
(\d -> (deltaM (mono (mu mm (fmap fm headDeltaM ((headDeltaM {l} {DeltaM M A (S O)} {monadM = mm}) d)))))) x))))
≡⟨ cong (\de -> deltaM (mono (mu mm de)))
(sym (covariant fm (\d -> (deltaM (mono (mu mm (fmap fm headDeltaM ((headDeltaM {l} {DeltaM M A (S O)} {monadM = mm}) d))))))  headDeltaM x)) ⟩
deltaM (mono (mu mm (fmap fm ((headDeltaM {A = A} {monadM = mm}) ∙
(\d -> (deltaM (mono (mu mm (fmap fm headDeltaM ((headDeltaM {l} {DeltaM M A (S O)} {monadM = mm}) d))))))) x)))
≡⟨ refl ⟩
deltaM (mono (mu mm (fmap fm (\d -> (headDeltaM {A = A} {monadM = mm} (deltaM (mono (mu mm (fmap fm headDeltaM ((headDeltaM {l} {DeltaM M A (S O)} {monadM = mm}) d))))))) x)))
≡⟨ refl ⟩
deltaM (mono (mu mm (fmap fm (\d -> (mu mm (fmap fm headDeltaM ((headDeltaM {l} {DeltaM M A (S O)} {monadM = mm}) d)))) x)))
≡⟨ refl ⟩
deltaM (mono (mu mm (fmap fm ((mu mm) ∙  (((fmap fm headDeltaM)) ∙  ((headDeltaM {l} {DeltaM M A (S O)} {monadM = mm})))) x)))
≡⟨ cong (\de -> deltaM (mono (mu mm de))) (covariant fm ((fmap fm headDeltaM) ∙ (headDeltaM)) (mu mm) x )⟩
deltaM (mono (mu mm (((fmap fm (mu mm)) ∙ (fmap fm ((fmap fm headDeltaM) ∙  (headDeltaM {l} {DeltaM M A (S O)} {monadM = mm})))) x)))
≡⟨ refl ⟩
deltaM (mono (mu mm (fmap fm (mu mm) ((fmap fm ((fmap fm headDeltaM) ∙ (headDeltaM {l} {DeltaM M A (S O)} {monadM = mm}))) x))))
≡⟨ cong (\de -> deltaM (mono (mu mm (fmap fm (mu mm) de)))) (covariant fm headDeltaM (fmap fm headDeltaM) x) ⟩
deltaM (mono (mu mm (fmap fm (mu mm) (((fmap fm (fmap fm headDeltaM)) ∙ (fmap fm (headDeltaM {l} {DeltaM M A (S O)} {monadM = mm}))) x))))
≡⟨ refl ⟩
deltaM (mono (mu mm (fmap fm (mu mm) (fmap fm (fmap fm headDeltaM) (fmap fm headDeltaM x)))))
≡⟨ cong (\de ->   deltaM (mono de)) (association-law mm (fmap fm (fmap fm headDeltaM) (fmap fm headDeltaM x))) ⟩
deltaM (mono (mu mm (mu mm (fmap fm (fmap fm headDeltaM) (fmap fm headDeltaM x)))))
≡⟨ cong (\de -> deltaM (mono (mu mm de))) (mu-is-nt mm headDeltaM (fmap fm headDeltaM x)) ⟩
deltaM (mono (mu mm (fmap fm headDeltaM (mu mm (fmap fm headDeltaM x)))))  ≡⟨ refl ⟩
deltaM (mono (mu mm (fmap fm headDeltaM (headDeltaM {A = DeltaM M A (S O)} {monadM = mm} (deltaM (mono (mu mm (fmap fm headDeltaM x))))))))  ≡⟨ refl ⟩
deltaM-mu (deltaM (mono (mu mm (fmap fm headDeltaM x))))  ≡⟨ refl ⟩
deltaM-mu (deltaM (mono (mu mm (fmap fm headDeltaM (headDeltaM  {A = DeltaM M (DeltaM M A (S O)) (S O)} {monadM = mm} (deltaM (mono x)))))))  ≡⟨ refl ⟩
deltaM-mu (deltaM-mu (deltaM (mono x)))  ∎
-}
deltaM-association-law {l} {A} {S n} M fm mm (deltaM (delta x d)) = begin
deltaM-mu (deltaM-fmap deltaM-mu (deltaM (delta x d)))
≡⟨ refl ⟩
deltaM-mu (deltaM (delta (fmap fm deltaM-mu x) (delta-fmap (fmap fm deltaM-mu) d)))
≡⟨ refl ⟩
deltaM (delta (mu mm (fmap fm (headDeltaM {A = A} {monadM = mm}) (headDeltaM {A = DeltaM M A (S (S n))} {monadM = mm} (deltaM (delta (fmap fm deltaM-mu x) (delta-fmap (fmap fm deltaM-mu) d))))))
(unDeltaM {A = A} {monadM = mm} (deltaM-mu (deltaM-fmap tailDeltaM (tailDeltaM (deltaM (delta (fmap fm deltaM-mu x) (delta-fmap (fmap fm deltaM-mu) d))))))))

≡⟨ refl ⟩
deltaM (delta (mu mm (fmap fm (headDeltaM {A = A} {monadM = mm}) (fmap fm deltaM-mu x)))
(unDeltaM {A = A} {monadM = mm} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-fmap (fmap fm deltaM-mu) d))))))
≡⟨ cong (\de -> deltaM (delta (mu mm de) (unDeltaM {A = A} {monadM = mm} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-fmap (fmap fm deltaM-mu) d)))))))
(sym (covariant fm deltaM-mu headDeltaM x)) ⟩
deltaM (delta (mu mm (fmap fm ((headDeltaM {A = A} {monadM = mm}) ∙  deltaM-mu) x))
(unDeltaM {A = A} {monadM = mm} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-fmap (fmap fm deltaM-mu) d))))))
≡⟨ cong (\de -> deltaM (delta (mu mm de)
(unDeltaM {A = A} {monadM = mm} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-fmap (fmap fm deltaM-mu) d)))))))
deltaM (delta (mu mm (fmap fm (((mu mm) ∙ (fmap fm headDeltaM)) ∙ headDeltaM) x))
(unDeltaM {A = A} {monadM = mm} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-fmap (fmap fm deltaM-mu) d))))))
≡⟨ refl ⟩
deltaM (delta (mu mm (fmap fm (((mu mm) ∙ (fmap fm headDeltaM)) ∙ headDeltaM) x))
(unDeltaM {monadM = mm} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM-fmap deltaM-mu (deltaM d))))))
≡⟨ cong (\de -> deltaM (delta (mu mm (fmap fm (((mu mm) ∙ (fmap fm headDeltaM)) ∙ headDeltaM) x))
(unDeltaM {monadM = mm} (deltaM-mu de))))
(sym (deltaM-covariant fm tailDeltaM deltaM-mu (deltaM d))) ⟩
deltaM (delta (mu mm (fmap fm (((mu mm) ∙ (fmap fm headDeltaM)) ∙ headDeltaM) x))
(unDeltaM {monadM = mm} (deltaM-mu (deltaM-fmap (tailDeltaM ∙ deltaM-mu) (deltaM d)))))
≡⟨ cong (\de -> deltaM (delta (mu mm (fmap fm (((mu mm) ∙ (fmap fm headDeltaM)) ∙ headDeltaM) x))
(unDeltaM {monadM = mm} (deltaM-mu de))))
(fmap-tailDeltaM-with-deltaM-mu (deltaM d))  ⟩
deltaM (delta (mu mm (fmap fm (((mu mm) ∙ (fmap fm headDeltaM)) ∙ headDeltaM) x))
(unDeltaM {monadM = mm} (deltaM-mu (deltaM-fmap ((deltaM-mu ∙ (deltaM-fmap tailDeltaM)) ∙ tailDeltaM) (deltaM d)))))
≡⟨ cong (\de -> deltaM (delta (mu mm de)
(unDeltaM {monadM = mm} (deltaM-mu (deltaM-fmap ((deltaM-mu ∙ (deltaM-fmap tailDeltaM)) ∙ tailDeltaM) (deltaM d))))))
deltaM (delta (mu mm (((fmap fm ((mu mm) ∙ (fmap fm headDeltaM))) ∙ (fmap fm headDeltaM)) x))
(unDeltaM {monadM = mm} (deltaM-mu (deltaM-fmap ((deltaM-mu ∙ (deltaM-fmap tailDeltaM)) ∙ tailDeltaM) (deltaM d)))))
≡⟨ refl ⟩
deltaM (delta (mu mm (((fmap fm ((mu mm) ∙ (fmap fm headDeltaM))) (fmap fm headDeltaM x))))
(unDeltaM {monadM = mm} (deltaM-mu (deltaM-fmap ((deltaM-mu ∙ (deltaM-fmap tailDeltaM)) ∙ tailDeltaM) (deltaM d)))))
≡⟨ cong (\de -> deltaM (delta (mu mm de)
(unDeltaM {monadM = mm} (deltaM-mu (deltaM-fmap ((deltaM-mu ∙ (deltaM-fmap tailDeltaM)) ∙ tailDeltaM) (deltaM d))))))
(covariant fm (fmap fm headDeltaM)  (mu mm) (fmap fm headDeltaM x)) ⟩

deltaM (delta (mu mm ((((fmap fm (mu mm)) ∙ (fmap fm (fmap fm headDeltaM))) (fmap fm headDeltaM x))))
(unDeltaM {monadM = mm} (deltaM-mu (deltaM-fmap ((deltaM-mu ∙ (deltaM-fmap tailDeltaM)) ∙ tailDeltaM) (deltaM d)))))
≡⟨ refl ⟩
deltaM (delta (mu mm (fmap fm (mu mm) (fmap fm (fmap fm headDeltaM) (fmap fm headDeltaM x))))
(unDeltaM {monadM = mm} (deltaM-mu (deltaM-fmap ((deltaM-mu ∙ (deltaM-fmap tailDeltaM)) ∙ tailDeltaM) (deltaM d)))))
≡⟨ cong (\de -> deltaM (delta de (unDeltaM {monadM = mm} (deltaM-mu (deltaM-fmap ((deltaM-mu ∙ (deltaM-fmap tailDeltaM)) ∙ tailDeltaM) (deltaM d))))))
(association-law mm (fmap fm (fmap fm headDeltaM) (fmap fm headDeltaM x))) ⟩
deltaM (delta (mu mm (mu mm (fmap fm (fmap fm headDeltaM) (fmap fm headDeltaM x))))
(unDeltaM {monadM = mm} (deltaM-mu (deltaM-fmap ((deltaM-mu ∙ (deltaM-fmap tailDeltaM)) ∙ tailDeltaM) (deltaM d)))))
≡⟨ cong (\de -> deltaM (delta (mu mm de) (unDeltaM {monadM = mm} (deltaM-mu (deltaM-fmap ((deltaM-mu ∙ (deltaM-fmap tailDeltaM)) ∙ tailDeltaM) (deltaM d))))))
deltaM (delta (mu mm (fmap fm headDeltaM (mu mm (fmap fm headDeltaM x))))
(unDeltaM {monadM = mm} (deltaM-mu (deltaM-fmap ((deltaM-mu ∙ (deltaM-fmap tailDeltaM)) ∙ tailDeltaM) (deltaM d)))))
≡⟨ cong (\de ->   deltaM (delta (mu mm (fmap fm headDeltaM (mu mm (fmap fm headDeltaM x)))) (unDeltaM {monadM = mm} (deltaM-mu de))))
(deltaM-covariant fm (deltaM-mu ∙ (deltaM-fmap tailDeltaM)) tailDeltaM (deltaM d)) ⟩
deltaM (delta (mu mm (fmap fm headDeltaM (mu mm (fmap fm headDeltaM x))))
(unDeltaM {monadM = mm} (deltaM-mu (((deltaM-fmap (deltaM-mu ∙ (deltaM-fmap tailDeltaM))  ∙ (deltaM-fmap tailDeltaM)) (deltaM d))))))
≡⟨ refl ⟩
deltaM (delta (mu mm (fmap fm headDeltaM (mu mm (fmap fm headDeltaM x))))
(unDeltaM {monadM = mm} (deltaM-mu (((deltaM-fmap (deltaM-mu ∙ (deltaM-fmap tailDeltaM)) (deltaM-fmap tailDeltaM (deltaM d))))))))
≡⟨ cong (\de -> deltaM (delta (mu mm (fmap fm headDeltaM (mu mm (fmap fm headDeltaM x)))) (unDeltaM {monadM = mm} (deltaM-mu de))))
(deltaM-covariant fm deltaM-mu (deltaM-fmap tailDeltaM) (deltaM-fmap tailDeltaM (deltaM d)))  ⟩
deltaM (delta (mu mm (fmap fm headDeltaM (mu mm (fmap fm headDeltaM x))))
(unDeltaM {monadM = mm} (deltaM-mu (((deltaM-fmap deltaM-mu) ∙ (deltaM-fmap (deltaM-fmap tailDeltaM))) (deltaM-fmap tailDeltaM (deltaM d))))))
≡⟨ refl ⟩
deltaM (delta (mu mm (fmap fm headDeltaM (mu mm (fmap fm headDeltaM x))))
(unDeltaM {monadM = mm} (deltaM-mu (deltaM-fmap deltaM-mu (deltaM-fmap (deltaM-fmap tailDeltaM) (deltaM-fmap tailDeltaM (deltaM d)))))))
≡⟨ cong (\de -> deltaM (delta (mu mm (fmap fm headDeltaM (mu mm (fmap fm headDeltaM x)))) (unDeltaM {monadM = mm} de)))
(deltaM-association-law M fm mm (deltaM-fmap (deltaM-fmap tailDeltaM) (deltaM-fmap tailDeltaM (deltaM d)))) ⟩
deltaM (delta (mu mm (fmap fm headDeltaM (mu mm (fmap fm headDeltaM x))))
(unDeltaM {monadM = mm} (deltaM-mu (deltaM-mu (deltaM-fmap (deltaM-fmap tailDeltaM) (deltaM-fmap tailDeltaM (deltaM d)))))))

≡⟨ cong (\de -> deltaM (delta (mu mm (fmap fm headDeltaM (mu mm (fmap fm headDeltaM x))))
(unDeltaM {monadM = mm} (deltaM-mu de))))
(sym (deltaM-mu-is-nt tailDeltaM (deltaM-fmap tailDeltaM (deltaM d)))) ⟩
deltaM (delta (mu mm (fmap fm headDeltaM (mu mm (fmap fm headDeltaM x))))
(unDeltaM {monadM = mm} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM-mu (deltaM-fmap tailDeltaM (deltaM d)))))))
≡⟨ cong (\de -> deltaM (delta (mu mm (fmap fm headDeltaM (mu mm (fmap fm headDeltaM x))))
(unDeltaM {monadM = mm} (deltaM-mu (deltaM-fmap tailDeltaM de)))))
(sym (deconstruct-id (deltaM-mu (deltaM-fmap tailDeltaM (deltaM d))))) ⟩
deltaM (delta (mu mm (fmap fm headDeltaM (mu mm (fmap fm headDeltaM x))))
(unDeltaM {monadM = mm} (deltaM-mu (deltaM-fmap tailDeltaM
(deltaM (unDeltaM {A = DeltaM M A (S (S n))} {monadM = mm} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM d)))))))))

≡⟨ refl ⟩
(unDeltaM {A = DeltaM M A (S (S n))} {monadM = mm} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM d))))))))))
(unDeltaM {monadM = mm} (deltaM-mu (deltaM-fmap tailDeltaM (tailDeltaM ((deltaM (delta (mu mm (fmap fm headDeltaM x))
(unDeltaM {A = DeltaM M A (S (S n))} {monadM = mm} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM d))))))))))))

≡⟨ refl ⟩
deltaM-mu (deltaM (delta (mu mm (fmap fm headDeltaM x))
(unDeltaM {A = DeltaM M A (S (S n))} {monadM = mm} (deltaM-mu (deltaM-fmap tailDeltaM (deltaM d))))))
≡⟨ refl ⟩
(unDeltaM {A = DeltaM M A (S (S n))} {monadM = mm} (deltaM-mu (deltaM-fmap tailDeltaM (tailDeltaM (deltaM (delta x d))))))))
≡⟨ refl ⟩
deltaM-mu (deltaM-mu (deltaM (delta x d)))
∎
{-
deltaM-association-law {l} {A} {S n} M fm mm (deltaM (delta x d)) = begin
deltaM-mu (deltaM-fmap deltaM-mu (deltaM (delta x d))) ≡⟨ refl ⟩
deltaM-mu (deltaM (delta-fmap (fmap fm deltaM-mu) (delta x d))) ≡⟨ refl ⟩
deltaM-mu (deltaM (delta (fmap fm deltaM-mu x) (delta-fmap (fmap fm deltaM-mu) d))) ≡⟨ refl ⟩
appendDeltaM (deltaM (mono (mu mm (fmap fm headDeltaM (fmap fm deltaM-mu x)))))
(deltaM-mu (deltaM-fmap tailDeltaM (deltaM (delta-fmap (fmap fm deltaM-mu) d)))) ≡⟨ refl ⟩
appendDeltaM (deltaM (mono (mu mm (fmap fm headDeltaM (fmap fm deltaM-mu x)))))
(deltaM-mu (deltaM (delta-fmap (fmap fm tailDeltaM) (delta-fmap (fmap fm deltaM-mu) d))))
≡⟨ cong (\de -> appendDeltaM (deltaM (mono (mu mm (fmap fm headDeltaM (fmap fm deltaM-mu x))))) de)
(sym (deconstruct-id (deltaM-mu (deltaM (delta-fmap (fmap fm tailDeltaM) (delta-fmap (fmap fm deltaM-mu) d)))))) ⟩

appendDeltaM (deltaM (mono (mu mm (fmap fm headDeltaM (fmap fm deltaM-mu x)))))
(deltaM (deconstruct {A = A} {mm = mm} (deltaM-mu (deltaM (delta-fmap (fmap fm tailDeltaM) (delta-fmap (fmap fm deltaM-mu) d))))))
≡⟨ refl ⟩
deltaM (deltaAppend (mono (mu mm (fmap fm headDeltaM (fmap fm deltaM-mu x))))
(deconstruct {A = A} {mm = mm} (deltaM-mu (deltaM (delta-fmap (fmap fm tailDeltaM) (delta-fmap (fmap fm deltaM-mu) d))))))
≡⟨ refl ⟩
deltaM (delta (mu mm (fmap fm headDeltaM (fmap fm deltaM-mu x)))
(deconstruct {A = A} {mm = mm} (deltaM-mu (deltaM (delta-fmap (fmap fm tailDeltaM) (delta-fmap (fmap fm deltaM-mu) d))))))
≡⟨ {!!} ⟩
appendDeltaM (deltaM (mono (mu mm (fmap fm headDeltaM (mu mm (fmap fm headDeltaM x))))))
(deltaM-mu (deltaM-fmap tailDeltaM (deltaM-mu (deltaM (delta-fmap (fmap fm tailDeltaM) d)))))
≡⟨ cong (\de -> appendDeltaM (deltaM (mono (mu mm (fmap fm headDeltaM (mu mm (fmap fm headDeltaM x))))))
(deltaM-mu (deltaM-fmap tailDeltaM de)))
(sym (deconstruct-id (deltaM-mu (deltaM (delta-fmap (fmap fm tailDeltaM) d))))) ⟩
appendDeltaM (deltaM (mono (mu mm (fmap fm headDeltaM (mu mm (fmap fm headDeltaM x))))))
(deltaM-mu (deltaM-fmap tailDeltaM (deltaM (deconstruct {A = DeltaM M A (S (S n))} {mm = mm} (deltaM-mu (deltaM (delta-fmap (fmap fm tailDeltaM) d)))))))

≡⟨ refl ⟩
appendDeltaM (deltaM (mono (mu mm (fmap fm headDeltaM (mu mm (fmap fm headDeltaM x))))))
(deltaM-mu (deltaM-fmap tailDeltaM (tailDeltaM ( (deltaM (delta (mu mm (fmap fm headDeltaM x))
(deconstruct {A = DeltaM M A (S (S n))} {mm = mm} (deltaM-mu (deltaM (delta-fmap (fmap fm tailDeltaM) d))))))))))
≡⟨ refl ⟩
(deconstruct {A = DeltaM M A (S (S n))} {mm = mm} (deltaM-mu (deltaM (delta-fmap (fmap fm tailDeltaM) d))))))))))))
(deltaM-mu (deltaM-fmap tailDeltaM (tailDeltaM ( (deltaM (delta (mu mm (fmap fm headDeltaM x))
(deconstruct {A = DeltaM M A (S (S n))} {mm = mm} (deltaM-mu (deltaM (delta-fmap (fmap fm tailDeltaM) d))))))))))
≡⟨ refl ⟩
deltaM-mu (deltaM (delta (mu mm (fmap fm headDeltaM x))
(deconstruct {A = DeltaM M A (S (S n))} {mm = mm} (deltaM-mu (deltaM (delta-fmap (fmap fm tailDeltaM) d))))))
≡⟨ refl ⟩
deltaM-mu (deltaM (deltaAppend (mono (mu mm (fmap fm headDeltaM x)))
(deconstruct {A = DeltaM M A (S (S n))} {mm = mm} (deltaM-mu (deltaM (delta-fmap (fmap fm tailDeltaM) d))))))
≡⟨ refl ⟩
deltaM-mu (appendDeltaM (deltaM (mono (mu mm (fmap fm headDeltaM x))))
(deltaM (deconstruct {A = DeltaM M A (S (S n))} {mm = mm} (deltaM-mu (deltaM (delta-fmap (fmap fm tailDeltaM) d))))))
≡⟨ cong (\de -> deltaM-mu (appendDeltaM (deltaM (mono (mu mm (fmap fm headDeltaM x)))) de))
(deconstruct-id (deltaM-mu (deltaM (delta-fmap (fmap fm tailDeltaM) d)))) ⟩
deltaM-mu (appendDeltaM (deltaM (mono (mu mm (fmap fm headDeltaM x))))
(deltaM-mu (deltaM (delta-fmap (fmap fm tailDeltaM) d))))
≡⟨ refl ⟩
deltaM-mu (appendDeltaM (deltaM (mono (mu mm (fmap fm headDeltaM x))))
(deltaM-mu (deltaM-fmap tailDeltaM (deltaM d))))≡⟨ refl ⟩
deltaM-mu (deltaM-mu (deltaM (delta x d)))
∎
-}

deltaM-is-monad : {l : Level} {A : Set l} {n : Nat}
{M : Set l -> Set l}
(functorM : Functor M)
Monad {l} (\A -> DeltaM M {functorM} {monadM} A (S n)) (deltaM-is-functor {l} {n})